Egypt - Linking Funding to Outputs : Expenditures of the Ministry of Agriculture and Land Reclamation - World Bank (World Bank, 2012)
This review of the on-budget expenditure of the Ministry of Agriculture and Land Reclamation (MALR) in Egypt describes the broad outline of the MARL's expenditures and identifies key themes and issues. The report examines how the context of the agricultural sector has changed, and the adjustment challenge that such change poses for the MALR. It explains how the MALR is thinking about the future, describes the structures of the MALR, and presents expenditure trends for the MALR down to the sector or authority level. Also, the document identifies some key issues to be addressed and zooms in on the research institutions of the MALR, the Agricultural Research Centre and the Desert Research Centre.